Chaperna-Mediated Assembly of Ferritin-Based Middle East Respiratory Syndrome-Coronavirus Nanoparticles - Kim, Young-Seok; Son, Ahyun; Kim, Jihoon; Kwon, Soon Bin; Kim, Myung Hee; Kim, Paul; Kim, Jieun; Byun, Young Ho; Sung, Jemin; Lee, Jinhee; Yu, Ji Eun; Park, Chan; et al. (Frontiers in Immunology, 2018)
The folding of monomeric antigens and their subsequent assembly into higher ordered structures are crucial for robust and effective production of nanoparticle (NP) vaccines in a timely and reproducible manner. Despite significant advances in in silico design and structure-based assembly, most engineered NPs are refractory to soluble expression and fail to assemble as designed, presenting major challenges in the manufacturing process. The failure is due to a lack of understanding of the kinetic pathways and enabling technical platforms to ensure successful folding of the monomer antigens into regular assemblages. Capitalizing on a novel function of RNA as a molecular chaperone (chaperna: chaperone + RNA), we provide a robust protein-folding vehicle that may be implemented to NP assembly in bacterial hosts. The receptor-binding domain (RBD) of Middle East Respiratory Syndrome Coronavirus (MERS)-CoV was fused with the RNA-interaction domain (RID) and bacterioferritin (FR), and expressed in E. coli in a soluble form. Site-specific proteolytic removal of the RID prompted the assemblage of monomers into nanoparticles, which was confirmed by electron microscopy and dynamic light scattering. The mutations that affected the RNA binding to RBD significantly increased the soluble aggregation into amorphous structures, reducing the overall yield of nanoparticles of a defined size. This underscored the RNA-antigen interactions during nanoparticle assembly. The sera after mouse immunization effectively interfered with the binding of MERS-CoV RBD to the cellular receptor hDPP4. The results suggest that RNA binding controls the overall kinetic network of the antigen folding pathway in favor of enhanced assemblage of NPs into highly regular and immunologically relevant conformations. The concentration of the ion Fe2+, salt, and fusion linker also contributed to the assembly in vitro, and the stability of the NPs. The kinetic 'pace-keeping' role of chaperna in the super molecular assembly of antigen monomers holds promise for the development and delivery of NPs and virus-like particles as recombinant vaccines and for serological detection of viral infections.